Solar Powered Smart Water Heater with Optimal Battery Management System - Dhole, Sakshi Sameer; Patil, Tejaswini Vitthal; Chavan, Rahul Arun; Meshram, Mavin Devendrakumar; Jadhav, Shital Sayaji (International Journal of Recent Advances in Multidisciplinary Topics, 2022)
In today’s covid pandemic situation, the large problem is unavailability of drinking warm water in hospitals. Drinking water heaters are hardly/mostly not available for the patients in the hospital. Our project deals with the designs an alternative for making hot water an economical drinking water heater system powered by the solar energy. We will easily be able to get hot drinkable water from any available water source. We are going to use here Single axis Tracking System on which our panel will be mounted, for getting the maximum output from the panel.
Keywords: Pandemic; Warm water; Tracking system; GSM; Alert